Analysis of PSAP (People Soft Account Payable) Information System in Improving Accountability at Hotel Z - WIRAPRADNYA, I Komang Bagus Triyana; YUSMARISA, Ni Luh Riska; MARENI, Ni Ketut (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to analyze the role of the PSAP (PeopleSoft Account Payable) information system in improving financial management accountability at Hotel Z. Accountability is an important element in organizational governance, particularly in the process of recording and paying company obligations. This study uses a descriptive qualitative approach with a case study method. Data collection techniques were carried out through direct observation, semi-structured interviews with financial staff (Accounts Payable, General Cashier, and Accounts Receivable), and documentation. Data were analyzed using the triangulation method and reviewed using two analytical frameworks, namely accountability indicators (SOP, supervision, responsibility, reporting, evaluation) and the PIECES framework (Performance, Information, Economics, Control, Efficiency, Service). The results of the study indicate that the implementation of PSAP has supported accountability through the presentation of accurate financial data, stricter supervision, and efficiency of the reporting process. However, there are still technical obstacles, such as decreased system performance during high transaction loads, errors at the closing of the accounting period, and user errors that result in duplicate payments. Based on these findings, it is recommended that management improve system capacity, conduct regular training for users, and carry out continuous evaluation to ensure the system runs optimally. This research contributes to strengthening information system-based accounting practices in the hospitality industry, as well as being a reference in decision-making related to accountable and efficient financial management.